Inventarisasi Jenis Pohon Inang Anggrek Epifit di Desa Tompobulu Resort Balocci Taman Nasional Bantimurung Bulusaraung Kabupaten Pangkep Provinsi Sulawesi Selatan - Sumarni, Sumarni; Hiola, St. Fatmah; Karim, Hilda (Fakultas MIPA UNM, 2019)
Abstract. Balocci Resort Banntimurung Bulusaraung National Park is a location that is overgrown with many natural orchids. This research is a descriptive study that aims to determine the type of epiphytic orchid host tree and the distribution of host trees at the Balocci Resort in Bantimurung Bulusearaung National Park. The method used is a survey method. The stages of the research are termining location and observations, collecting data and indetifying spesies. Based on the result; AlstoniaÂ scholaris, Sauarauia malayana, Mangifera sp, Tabernaemontana sphaerocarpa, Arenga pinnata, Syzygium sp, Elaecarpus angustifolius, Bischofia javanica, Maesea sp, Erythrina subumbrans, Lithocarpus celebicus, Cryptocarya sp, Elmerillia ovalis, Memecylon paniculatum, Ficus benjamina L, Ficus variegate, Ficus fistulosa, Knema laurina, Litsea sp, Uncaria longiflora, Coffea sp, Melicope sp, Planchonella firma, Palaquium lobbianum, and Laportea stimulant which belongs to 19 families. The tree that is overgrows with orchids is AlstoniaÂ scholaris, Sauarauia malayana and Ficus benjamina L. the host tree which is used as a place for growth has uneven surface characteristics of the tree, overgrown with nails and generally mossy. Host tree species that have a wide spread on mount Bulusaraung is Sauarauia malayana which is at an altitude of 700-1300 m above sea level. Keywords: host tree, epiphytic, resort balocci, bantimurung bulusaraung national park area